2014
DOI: 10.1093/hmg/ddu316
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans dnj-14, the orthologue of the DNAJC5 gene mutated in adult onset neuronal ceroid lipofuscinosis, provides a new platform for neuroprotective drug screening and identifies a SIR-2.1-independent action of resveratrol

Abstract: Adult onset neuronal lipofuscinosis (ANCL) is a human neurodegenerative disorder characterized by progressive neuronal dysfunction and premature death. Recently, the mutations that cause ANCL were mapped to the DNAJC5 gene, which encodes cysteine string protein alpha. We show here that mutating dnj-14, the Caenorhabditis elegans orthologue of DNAJC5, results in shortened lifespan and a small impairment of locomotion and neurotransmission. Mutant dnj-14 worms also exhibited age-dependent neurodegeneration of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 54 publications
3
60
2
Order By: Relevance
“…For example, a spontaneous genetic mutation that robustly delays synaptic degeneration (known as Wld S ) can ameliorate neurodegeneration across a range of conditions, including some forms of motor neuron disease (Ferri et al 2003), Parkinson's disease (Sajadi et al 2004) and following global cerebral ischemia (Gillingwater et al 2004) or traumatic brain injury . Furthermore, at the molecular level, a number of individual synaptic proteins that can modulate synaptic vulnerability and degeneration in response to a variety of pathological stimuli have recently been identified, including CSP alpha/DNAJC5 (Fern andez-Chac on Garc ıa-Junco-Clemente et al 2010;Noskov a et al 2011;Wishart et al 2012;Kashyap et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a spontaneous genetic mutation that robustly delays synaptic degeneration (known as Wld S ) can ameliorate neurodegeneration across a range of conditions, including some forms of motor neuron disease (Ferri et al 2003), Parkinson's disease (Sajadi et al 2004) and following global cerebral ischemia (Gillingwater et al 2004) or traumatic brain injury . Furthermore, at the molecular level, a number of individual synaptic proteins that can modulate synaptic vulnerability and degeneration in response to a variety of pathological stimuli have recently been identified, including CSP alpha/DNAJC5 (Fern andez-Chac on Garc ıa-Junco-Clemente et al 2010;Noskov a et al 2011;Wishart et al 2012;Kashyap et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutation of a Drosophila PAT, HIP14, causes a strong impairment of neurotransmission that is entirely due to non-palmitoylation of cysteine string protein (CSP), as expression of a chimaeric CSP artificially targeted to synapses fully rescues this defect [ 59 ]. However, the extremely severe phenotype of CSP mutants seen in Drosophila [ 60 ] is not observed in C. elegans null mutants [ 61 ], so even if mutation of a worm PAT(s) completely prevented CSP palmitoylation, this would not result in strong effects on the phenotypes analysed in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the absence of CSPα leads to neurodegeneration in drosophila, mice and c. elegans 20,41,77 . In vitro, DnaJB6 inhibits Aβ amyloid aggregation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that the molecular co-chaperone, CSPα (cysteine string protein, DnaJC5) promotes EV export of distinct misfolded disease-causing proteins and that this export pathway is 'druggable' as demonstrated by the ability of the polyphenol, resveratrol, to block CSPα-mediated export of misfolded proteins 15 . Resveratrol was initially linked to CSPα function in a chemical screen as a compound that alters life span of CSPα c. elegans mutants 41 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation